Pengaruh Kepemilikan Manajerial, Return on Assets, dan Leverage Terhadap Discretionary Earnings Management Pada Perusahaan Ipo di Bursa Efek Indonesia Periode 2018 – 2020 - Dita Prada Claudia; Chasan Azari; Setya Prihatiningtyas (Journal Of Accounting and Business, 2023)
The purpose of ths study was analyze the influence of managerial proportion, return on assets, and leverage on discretionary earnings management in IPOs companies which listed in Indonesia Stock Exchange period 2018 until 2020. The purpose of this study is to examine and analyze the effect of managerial ownership, return on assets, and leverage on discretionary earnings management. IPOs are now widely adopted by the Company as a solution to obtain additional capital and also as a separate value that can improve the Company's image to investors. Achieving good profits is closely related to the Company's success in attracting more investors. Discretionary earning management activity as a solution for managers who have ownership proportions to manage the level of profit achievement by paying attention to the level of return on assets & leverage in the initial period when listing on the Indonesia Stock Exchange so that it can attract more investors for the success of the Company in managing its operations. The amount of managerial ownership in this study is measured by Managerial Proportion (MNJ), Return on Assets is measured by ROA, and Leverage is measured by Debt Equity Ratio (DER). This type of research is associative with a quantitative approach. The population used in this study were companies that conducted IPOs on the IDX in the period 2018 - 2020. The determination of the sample in this study used a purposive sampling technique with certain criteria, so as many as 13 companies were obtained. The data analysis technique used is multiple linear regression. The results of this study indicate that MNJ, ROA, and DER simultaneously or together have an effect on discretionary earnings management